Faktor Determinan Kejadian Stunting Pada Anak Usia 13 sampai 24 Bulan Di Desa Wilayah Kerja Puskesmas Poncokusumo Kabupaten Malang - Putri Nurbaiti; Budi Suharno; Desy Dwi Cahyani (Poltekkes Kemenkes Malang, 2019)
Stunting is a condition of incompatibility between a child height and age. Stunting problem is a matter that needs to be considered because it can reduce one productivity, so that it will produce poor human resources. Poncokusumo Subdistrict is one of areas where stunting is still high, 1.941 toddlers with 59,7 percent short category and 40,3 percent too short category. This study aims to determine the determinants factors of the stunting case in children aged 13 until 24 months in the Village of Community Health Centre Work Area of Poncokusumo. The populations used were 86 children, while the samples were 71 stunting children aged 13 until 24 months in the Village of Community Health Centre Work Area of Poncokusumo. The distributions of children each posyandu in each village were Gubugklakah Village namely 8 children, Karangnongko Village namely 25 children, Belung Village namely 21 children, Ngebruk Village namely 16 children, Pajajaran Village namely 1 child. Sampling in this study used the propotionate startified random sampling technique with a retrospective approach. The research instrument used interview sheets and documentation studies on the KIA book, then it would be analyzed using descriptive analysis with the results that half of the respondent mother education were junior high school namely 50.7 percent and almost half of the respondents did not get Exclusive ASI namely 54.9 percent, and almost half of the respondents did not get MP ASI correctly namely 56.3 percent. Intervention is needed that focus on maternal and child health to reduce the stunting case, and to foster maternal awareness of the importance of Exclusive ASI and the Accuracy of giving MP ASI to children through counseling